Combined effects of photoaging and natural organic matter on the colloidal stability of nanoplastics in aquatic environments. (1st November 2022) - Xu, Yanghui; Ou, Qin; Li, Xiaoming; Wang, Xintu; van der Hoek, Jan Peter; Liu, Gang
Highlights: Combined effects of photoaging and NOM on aggregation kinetics of NPs were investigated. Photoaged NPs adsorbed less HA and more BSA than the pristine NPs. HA and pristine NPs competed for photons and underwent photo-degradation. Light radiation induced photo-flocculation of BSA molecules, wrapped and integrated NPs. Sequence of photoaging and NOM attachment has essentially different effects on NPs stability. Abstract: The transport and fate of nanoplastics (NPs) in aquatic environments are closely associated with their colloidal stability, which is affected by aging and natural organic matter (NOM) adsorption. This study systematically investigated the combined effects of photoaging and NOM (e.g. humic acids, HA; and a model protein, bovine serum albumin, BSA) on the aggregation kinetics of NPs (polystyrene, PS) in NaCl and CaCl2 solutions. Our results showed that photoaged NPs adsorbed less HA than pristine NPs due to weaker hydrophobic and π-π interactions. In return, HA showed weaker impacts on NPs' stability after photoaging. Differently, photoaged NPs absorbed more BSA than pristine NPs due to stronger hydrogen bonding and electrostatic attraction. Thus, the inhibitory effects of BSA on the aggregation kinetics of NPs were enhanced after photoaging. Regarding the effects of NOM on the aging of NPs, our results showed that HA competed with NPs for photons and underwent photo-degradation. Subsequently, the destruction/reconstruction of adsorbed HA increased (in NaCl) or decreased (in CaCl2 ) the stability of NPs. Notably, light radiation-induced flocculation of BSA molecules, which wrapped and integrated NPs and lead to their destabilization. Overall, this study provided new insights into the aggregation behavior of NPs in aquatic systems, which have significant implications for predicting the transport and fate of NPs in complex real-world environments. Graphical abstract: Image, graphical abstract